Molecular basis of hereditary fructose intolerance in Italy: identification of two novel mutations in the aldolase B gene. Issue 9 (September 1996) - Santamaria, R; Tamasi, S; Del Piano, G; Sebastio, G; Andria, G; Borrone, C; Faldella, G; Izzo, P; Salvatore, F
Abstract : We screened the aldolase B gene in 14 unrelated Italian patients with hereditary fructose intolerance (HFI), and found two novel disease related mutations: a single nucleotide deletion in exon 2 (delta A20) that leads to an early stop codon, and a C-->T transition in exon 8 that substitutes an Arg with a Trp residue at codon 303 (R303W).